Surface solvation of Martian salt analogues at low relative humidities. Issue 2 (10th February 2022) - Kong, Xiangrui; Zhu, Suyun; Shavorskiy, Andrey; Li, Jun; Liu, Wanyu; Corral Arroyo, Pablo; Signorell, Ruth; Wang, Sen; Pettersson, Jan B. C.
Abstract : Salt aerosols play important roles in many processes related to atmospheric chemistry and the climate systems on both Earth and Mars. Abstract : Salt aerosols play important roles in many processes related to atmospheric chemistry and the climate systems on both Earth and Mars. Complicated and still poorly understood processes occur on the salt surfaces when interacting with water vapor. In this study, ambient pressure X-ray photoelectron spectroscopy (APXPS) is used to characterize the surface chemical environment of Martian salt analogues originating from saline lakes and playas, as well as their responses to varying relative humidities. Generally, APXPS shows similar ionic compositions to those observed by ion chromatography (IC). However, XPS is a surface-sensitive method while IC is bulk-sensitive and differences are observed for species that preferentially partition to the surface or the bulk. Element-selective surface enhancement of Cl − is observed, likely caused by the presence of SO4 2− . In addition, Mg 2+ is concentrated on the surface while Na + is relatively depleted in the surface layer. Hence, the cations (Na + and Mg 2+ ) and the anions (Cl − and SO4 2− ) show competitive correlations. At elevated relative humidity (RH), no major spectral changes were observed in the XPS results, except for the growth of an oxygen component originating from condensed H2 O. Near-edge X-ray absorption fine structure (NEXAFS) measurements show that the magnesium and sodium spectra are sensitive to the presence of water, and the results imply that the surface is fully solvated already at RH = 5%. The surface solvation is also fully reversible as the RH is reduced. No major differences are observed between sample types and sample locations, indicating that the salts originated from saline lakes commonly have solvated surfaces under the environmental conditions on Earth.